Ways to Improve the Supply Chain Management Mechanism of the Firm's Competitiveness - Ahmad Hassan Ahmad Ahmed (International Journal of Supply Chain Management, 2019)
In the era of globalization and internationalization of the economy, competitiveness is one of the main criteria for its effectiveness. Today it is impossible to find a market in which there is no competition, so the problem of competitiveness of the firm is relevant and requires constant research. There are many definitions of the concept of managing a firm's competitiveness. In this article, after analyzing the different approaches, a generalized definition is derived. In unstable market conditions, the success of the firm in the market depends on its competitiveness, timely establishment of strategic goals, flexibility of the production system, which is ensured by the accuracy and timeliness of management decisions.Effective management of the firm in the market conditions is essentially reduced to the management of its competitiveness (to the assessment and analysis of factors that increase or decrease the competitiveness of the firm, the choice and implementation of appropriate strategies and tactics to achieve a particular goal). Since today in the world of high technology it is more difficult for a firm to survive, the firms themselves, which use as many methods of management as possible, will be more interesting for investors, what is the result of the introduction of certain innovations. The purpose of management in this situation is to react to innovations and changes in time. The article highlights a number of key factors affecting the competitiveness of the firm and management decision-making, the management tools of competitiveness management.